Will Nanotechnology Bring New Hope for Gene Delivery?. Issue 5 (May 2017) - Wong, Joanna K.L.; Mohseni, Rashin; Hamidieh, Amir Ali; MacLaren, Robert E.; Habib, Nagy; Seifalian, Alexander M.
Abstract : The high mortality rates of cancer patients receiving standard treatments emphasize the crucial need for alternative treatments. One promising strategy is to use organic nanoparticles (NPs) for gene delivery. Although multifunctional NPs theoretically have many desirable properties as gene vectors, there are several practical barriers to successful gene delivery. In this review we discuss the properties of NPs and overview in vitro and preclinical studies of organic NPs over the past 5 years. The results of recent clinical trials suggest that the NP field holds significant promise. The annual market value for successful gene delivery could exceed US30 billion, and this will encourage researchers to study the application of NPs to therapeutic gene delivery. Trends: Gene therapy is a concept that has fascinated the scientific community for years. Its popularity is evident from emerging concepts such as CRISPR-based genome editing and epigenetic studies, and has been applied in diseases with hematological, ophthalmological, genetic, and neurological origins. The popularity of fields such as proteomics, metabolomics, and transcriptomics will only hasten the impending successes of gene therapy. Methods for NP synthesis are evolving. Researchers are developing easier ways of synthesizing a wide variety of NPs, and this field combines multiple areas of endeavor including bioengineering, design, chemistry, and physics. Amalgamating the two concepts, the use of NPs in gene delivery is a field to watch closely, and we anticipate a breakthrough in the next decade.